A Clinical Comparative Study on The Efficacy of Sahacharadi Kwath with and without Matra Basti in the Management of Janu Sandhigat Vata w.s.r. to Osteo Arthritis (International Journal of Ayurveda and Pharma Research, 2022)
Sandhigat Vata is a Vata vyadhi of degenerative nature, and Basti is preferred line of treatment for all Vata vyadhi as mentioned by Acharya Charak. Matra Basti is a type of Anuvasan Basti which is used for many degenerative diseases. So for present study Matra Basti with Sahachar Tail was selected. Acharya Charaka has mentioned Sahachar Taila in the management of the Vat Vyadhi. Acharya Yogratnakar has mentioned Sahacharadi Kwath with Til Taila under the context of Vat Vyadhi. Here Sahacharadi Kwath with Til Taila was selected for Shaman Chikitsa.Aims and objectives: To evaluate and compare the effect of Sahacharadi Kwath with and without Matra Basti in the management of Janu Sandhigat Vata w.s.r to Osteo-arthritis.Material and methods: For present study 30 patients of Janu Sandhigat Vata were selected according to the classical signs and symptoms of Sandhigat Vata according to Ayurveda as well as modern science, were randomly divided into 2. Result: In Group A, total 15 patients were treated. Out of 15 patients 20.0% patients got marked improvement, 73.33% got moderate improvement while 6.67% patients got mild improvement. No patient got complete remission. In Group B, total 15 patients were treated. Out of them 6.67% patients got marked improvement, 40.0% patients got moderate improvement and 46.67% showed mild improvement. One patient remains unimproved. No patient got complete remission. Conclusion: It is concluded that Matra Basti along with Sahacharadi Kwath provided better result as compare to only Sahacharadi Kwath in the management of Janu Sandhigata Vata.